Separated multi streams transmitting method based on SIP+P2P system - LEI Wei-min1; ZHANG Xiu-wu2; JIA Jun-ying3; YU Bo3 (Tongxin xuebao)
A separated multiple media traffics transmitting method was proposed to solve the QoS problem of multi-service streaming.Based on SIP+P2P system,this method leveraged path diversity,selected different paths for each media stream,and switched path separately.By distributing multiple media streams into different single paths which had path diversity,this approach eliminated the affect on path quality introduced by high throughput media traffic.The NS2 simulation and real network test results show that the approach than the original single-path transmission method could further improve the quality of the path,and could effectively improve the service quality of multi-service streaming.